Efektivitas Fungi Mikoriza Arbuskula pada Tanaman Singkong (Manihot esculenta) di Tanah Inceptisol Bogor - Khairiyah, Yaumil; Widyastuti, Rahayu; Badia Ginting, Rohani Cinta (Jurnal Ilmu Pertanian Indonesia, 2022)
Cassava is widely grown in Inceptisol. As agricultural land, the soil has several problems, i.e., high soil acidity, easily leached soil surface layers, unstable soil aggregates, and slow permeability. Arbuscular mycorrhizal fungi (AMF) form a symbiotic relationship with over 80% of higher plant species. However, the effectiveness of AMF on cassava has not been widely reported. This study aimed to determine the effect of AMF inoculants on the vegetative growth of cassava in Inceptisol. The AMF inoculants used were Gigaspora sp., Glomus manihotis, and a consortium of Acaulospora tuberculata and Glomus rubiforme. The experiment was performed in a Randomized Block Design with 8 treatments and 3 replications, i.e., M1 = G. manihotis; M2 = Gigaspora sp.; M3 = consortium of A. tuberculata-G. rubiforme; M4 consortium of G. manihotis-Gigaspora sp.; M5 consortium of G. manihotis-A. tuberculata-G. rubiforme; M6 consortium of A. tuberculata-G. rubiforme-Gigaspora sp.; and M7 consortium of G. manihotis-A. tuberculata-G. rubiforme-Gigaspora sp.; and control (as recommended dose of NPK fertilizers). In the AMF application treatment, 75% of the recommended NPK fertilizer was applied, thus saving 25% from the control. A total of 50 AMF spores were applied to each cassava plant and maintained for 8 weeks. The data were analyzed using the RStudio 4.1.1 program. The results showed that all treatments with AMF gave various effectiveness and could compete with the indigenous AMF. AMF application significantly increased the vegetative growth of cassava grown in Inceptisols, i.e., shoot and root dry weight, root length, P-uptake, and percentage of root infection. Application of G. manihotis and the consortium of A. tuberculata-G. rubiforme-Gigaspora sp. effectively increased cassava plants' growth for 8 weeks in Inceptisol. The AMF application could save 25% on the use of NPK fertilizers. Keywords: Acaulospora, cassava, Gigaspora, Glomus, fertilizer, mycorrhizal